2014
DOI: 10.12657/denbio.072.008
|View full text |Cite
|
Sign up to set email alerts
|

Climate influence on radial growth of Fagus sylvatica growing near the edge of its distribution in Bükk Mts., Hungary

Abstract: Future of beech (Fagus sylvatica L.) in a changing climate is one of the greatest debates in Europe among the studies dealing with the climate change generated xeric limit shifting. We investigated a submontane beech stand's growth response to climate change in Northern Hungary during the past 60 years following dendrochronological methods. Tree-ring width data were processed using three alternatives of standardization. To recover the basic climate-growth relationships for beech we analyzed the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
5
13
0
1
Order By: Relevance
“…This is in accordance with the study by Bhuyan et al (2017). Other studies from the wider region have highlighted the importance of above average precipitation for the growth of beech (Čufar et al, 2008b;Di Filippo et al, 2007;Garamszegi & Kern, 2014) and they also connect the response with the occurrence of drought. Only Tegel et al (2014) found the temperature signal to be more important than the drought signal, although they also found that the latter (scPDSI) is almost equally important as the temperature signal.…”
Section: Discussion Correlation Between Growth and Spisupporting
confidence: 90%
“…This is in accordance with the study by Bhuyan et al (2017). Other studies from the wider region have highlighted the importance of above average precipitation for the growth of beech (Čufar et al, 2008b;Di Filippo et al, 2007;Garamszegi & Kern, 2014) and they also connect the response with the occurrence of drought. Only Tegel et al (2014) found the temperature signal to be more important than the drought signal, although they also found that the latter (scPDSI) is almost equally important as the temperature signal.…”
Section: Discussion Correlation Between Growth and Spisupporting
confidence: 90%
“…The above presented pattern of climate-growth relationship, namely the positive dominance of summer precipitation and negative impact of summer temperature was reported in other studies in Hungary on beech (Garamszegi & Kern, 2014) and on oak (Kern et al, 2013) and was observed many times on pine (Koprowski, 2012;Michelot, 2012;Panayotov et al, 2013;Levanič, 2015;Toromani et al, 2015) as well. However, we found a much unusual pattern also, which has never been observed in Hungary neither on pines nor on other species, but rare in the MJJ (May-June-July), JJA (June-July-August), SPR (March-April-May) and VGP (March-October) represent the combined periods, GWL shows groundwater data.…”
Section: Discussionsupporting
confidence: 77%
“…Campelo et al, 2007Campelo et al, , 2013Cufar et al, 2011;de Luis et al, 2011;De Micco et al, 2014;Olivar et al, 2012) but researches have already been made in temperate forests as well (Ježík, 2011;Nabais et al, 2014;Panayotov et al, 2013;van der Werf, 2007). Tree-ring studies in Hungary have been focused on climate-growth relationship (Babos, 1984;Garamszegi & Kern, 2014;Kern et al, 2013;Szabados, 2006) and climate reconstruction (Kern et al, 2009) so far, thus dendrochronological approach of the investigation of negative extreme climatic events is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…A positive response to summer rainfall has been evidenced for a variety of broadleaved species from temperate forests in Europe (García-Suarez et al, 2009;Scharnweber et al, 2011;Čufar et al, 2014;Garamszegi & Kern, 2014;Rozas et al, 2015) and North America (Tardif et al, 2001;Bishop et al, 2015). Accordingly, summer rainfall in July-August controlled radial growth of Acer, Fagus and Fraxinus.…”
Section: Discussionmentioning
confidence: 97%